Conductive silver paste and its preparation method and application

Through specific resin selection and conductive silver ratio adjustment, conductive silver paste with high dispersion and stability was prepared. The composite technology of micron silver sheets and nano silver powder was used to solve the problems of insufficient conductivity, adhesion and weatherability, and the application of flexible touch screen with high light transmittance and high performance was achieved.

CN115083658BActive Publication Date: 2025-03-21NANO TOP ELECTRONICS TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210748780.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2025-03-21
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

The existing conductive silver paste has problems of insufficient conductivity, adhesion and weather resistance in applications requiring high light transmittance, making it difficult to meet the high performance needs of flexible touch screens.

Method used

By selecting a specific type of resin and adjusting the ratio of resin to conductive silver, conductive silver paste with high dispersion and stability is prepared. The slurry uses a composite of micron silver sheets and nano-silver powder to ensure that at least 4 layers of overlap are formed in wire grooves with a width of ≤2μm, improving conductivity and improving weather resistance.

Benefits of technology

It realizes excellent conductivity, boiling resistance and high weather resistance of conductive silver paste, and is suitable for conventional metal grid flexible conductive films with high requirements for light transmittance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003717531040000151
    Figure BDA0003717531040000151
  • Figure BDA0003717531040000161
    Figure BDA0003717531040000161
  • Figure BDA0003717531040000171
    Figure BDA0003717531040000171
Patent Text Reader

Abstract

The present invention provides a conductive silver paste and a preparation method and application thereof. The raw materials for preparing the conductive silver paste include, by weight, 66-72 parts of a functional component, 3-6 parts of an auxiliary agent, and 25-28 parts of an organic solvent; the functional component includes a resin and conductive silver in a mass ratio of 1:(5-12); the resin includes a saturated polyester resin and an acrylic resin. The present invention provides a conductive silver paste having excellent conductive properties, water boiling resistance, and high weather resistance through a specific arrangement of the resin and the conductive silver in the functional component, and can be used for the preparation of a metal mesh flexible conductive film with high light transmittance requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible touch screens and relates to a conductive material, in particular to a conductive paste and a preparation method and application thereof. Background Art

[0002] Touch screens have been widely used in people's daily lives. With the in-depth development of the electronic information industry and the continuous growth in demand for consumer electronic products, smart terminals such as smartphones, tablets, and touch-screen notebooks will become more popular, and various industrial products are also increasingly using touch operation interfaces to meet their intelligent and digital requirements.

[0003] Traditional touch screens use ITO (indium tin oxide) coated on transparent substrates such as PET or peeling, and use etching, acid engraving and other methods to make patterns on the ITO coating, and then use chips to connect the channels in the TIO pattern to record the current changes that occur during the touch process, thereby realizing the position calculation of the touch point. However, when the surface resistance of ITO is low, there are problems of performance degradation and easy breakage. The traditional ITO conductive film is a rigid material and is not suitable for folding mobile phones. Therefore, a flexible material is needed to replace it. The traditional material that currently replaces ITO materials is metal grid flexible conductive materials.

[0004] Metal mesh flexible conductive material is a conductive material formed by printing grid pattern grooves on polymer film and filling nano-conductive silver paste into the grooves by embossing and scraping to solidify. The flexibility, low surface resistance and high light transmittance of metal mesh flexible conductive material are mainly achieved by the bending resistance, high conductivity and ultra-fine line filling of nano-imprinted conductive silver paste. The better the bendability of nano-imprinted conductive silver paste, the higher the flexibility of metal mesh flexible conductive material; the higher the conductivity of nano-imprinted conductive silver paste, the lower the surface resistance of metal mesh flexible conductive material; the smaller the particle size in nano-imprinted conductive silver paste, the lower the fillable line width, and the higher the light transmittance of metal mesh flexible conductive material.

[0005] CN 105702323A discloses a flexible conductive silver paste and a preparation method thereof, wherein the components and mass percentages of the flexible conductive silver paste are as follows: 30-60% silver nanowires, 1-5% hydroxyethyl methacrylate phosphate, 18-30% solvent, 15-30% polyurethane resin, 5-10% polyvinyl butyral, 0.5-2% defoamer, and 0.5-5% curing agent. Hydroxyethyl methacrylate phosphate is used to generate a contacting effect with the silver nanowires and the polyurethane resin, thereby improving the stability of the silver nanowires and obtaining a flexible conductive silver paste with excellent adhesion and bending resistance, but the invention does not involve the improvement of the weather resistance of the conductive silver paste.

[0006] CN 112908513A discloses a conductive silver paste for flexible circuits and a preparation method thereof, wherein the conductive silver paste for flexible circuits comprises the following components and their weight percentages: epoxy modified flexible resin 5-12wt%, organic solvent 30-50wt%, conductive silver powder 40-55wt%, nano silver powder 3-15wt%, leveling agent 0.5-2wt%, thickener 0.5-2wt%, defoamer 0.5-2wt%, curing agent 0.5-5wt%, wherein the particle size of the conductive silver powder is micron-level. The conductive silver paste introduces epoxy groups through epoxy modified flexible resin, thereby improving the adhesion between the silver paste and the substrate and ensuring good flexibility, but it also does not involve the improvement of the weather resistance of the conductive silver paste.

[0007] CN 113436781A discloses a wear-resistant conductive paste and a preparation method thereof. The conductive paste comprises, by weight, 0.1-1 part of a water boiling adhesion promoter, 0.5-1 part of an ink overflow prevention agent, 0.2-1 part of a defoamer, 0.2-0.5 part of a dispersant, 0.1-0.2 part of a curing agent promoter, 5-40 parts of an organic solvent, 10-50 parts of a wear-resistant filler, 20-40 parts of flaky silver powder, 5-30 parts of a resin and 0.5-0.8 parts of a curing agent. The conductive paste adopts an acrylic acid-modified polyurethane resin as a bonding phase, thereby improving the water boiling performance and bending resistance of the conductive paste and having good storage stability. Different low-temperature curing agents are used for compounding to ensure that other properties are improved in terms of the adhesion of the paste in a constant temperature and humidity environment. The conductive silver powder and the wear-resistant filler are added to make the paste have higher wear resistance and lower conductivity, but the conductive paste also does not involve the improvement of the weather resistance of the conductive silver paste.

[0008] Moreover, the requirements for the transmittance of touch screens are getting higher and higher. To improve the transmittance of touch screens, it is necessary to reduce the width of the line groove in the substrate while ensuring the conductive performance. This also puts higher requirements on the conductive performance of the conductive silver paste, the adhesion to the substrate, and the weather resistance. Summary of the invention

[0009] In view of the deficiencies in the prior art, the object of the present invention is to provide a conductive silver paste and a preparation method and application thereof. The conductive silver paste has high dispersibility and good stability, good conductivity, water boiling resistance and high weather resistance, and the preparation method is simple and reliable, with low cost, which is convenient for industrial promotion.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a conductive silver paste, wherein the raw materials for preparing the conductive silver paste include, by weight:

[0012] 66-72 parts of functional components;

[0013] 3-6 parts of additives;

[0014] 25-28 parts of organic solvent;

[0015] The functional component comprises a resin and conductive silver in a mass ratio of 1:(5-12);

[0016] The resin includes saturated polyester resin and acrylic resin.

[0017] In parts by weight, the raw materials for preparing the conductive silver paste of the present invention include 66-72 parts of functional components, for example, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts or 72 parts, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In parts by weight, the raw materials for preparing the conductive silver paste of the present invention include 3-6 parts of additives, for example, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In parts by weight, the raw materials for preparing the conductive silver paste of the present invention include 25-28 parts of organic solvent, for example, it can be 25 parts, 25.5 parts, 26 parts, 26.5 parts, 27 parts, 27.5 parts or 28 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] The functional components include resin and conductive silver, and the mass ratio of the resin to the conductive silver is 1:(5-12), for example, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] The present invention makes specific selection of resin types and specific setting of the ratio of resin to conductive silver, so that the final conductive silver paste has excellent conductivity, water boiling resistance and high weather resistance, and is suitable for conventional metal grid flexible conductive films with high requirements for light transmittance.

[0022] Preferably, the mass ratio of the saturated polyester resin to the acrylic resin is (4-6):1, for example, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the number average molecular weight of the saturated polyester resin is 25000-50000, for example, 25000, 30000, 35000, 40000, 45000 or 50000, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the number average molecular weight of the acrylic resin is 250,000-300,000, for example, 250,000, 260,000, 270,000, 280,000, 290,000 or 300,000, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] Preferably, the conductive silver comprises micron silver flakes and nano silver powder in a mass ratio of 2:(1-3).

[0026] The mass ratio of the micronized slices to the nano silver powder of the present invention is 2:(1-3), for example, it can be 2:1, 2:1.5, 2:2, 2:2.5 or 2:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the thickness of the micronized silver flakes is 1-3 μm, and the equivalent diameter is 2-5 μm.

[0028] The thickness of the micronized silver flakes of the present invention is 1-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] The equivalent diameter of the micronized silver flakes of the present invention is 2-5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] The thickness and equivalent diameter of the micron silver flakes described in the present invention refer to the average thickness and average equivalent diameter of the micron decoction pieces.

[0031] Preferably, the nano silver powder has a particle size range of 50-500 nm, and a median particle size D50 of 100-200 nm.

[0032] The particle size range of the nano silver powder of the present invention is 50-500nm, which means that the minimum particle size of the nano silver powder is above 50nm, for example, it can be 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the maximum particle size of the nano silver powder is below 500nm, for example, it can be 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm or 500nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0033] The median particle size D50 of the nano silver powder of the present invention is 100-200 nm, for example, it can be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] The present invention combines micron silver flakes with nano silver powder to form at least 4 interlayer overlaps in a wire slot with a width of ≤2μm, thereby eliminating abnormal phenomena such as uneven resistance and short circuits, and achieving a significant improvement in conductive performance.

[0035] Preferably, the organic solvent comprises any one of DBE, dimethyl oxalate, diethyl oxalate or dipropylene glycol methyl ether, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of DBE and dimethyl oxalate, a combination of dimethyl oxalate and diethyl oxalate, a combination of diethyl oxalate and dipropylene glycol methyl ester, a combination of dimethyl oxalate, dimethyl oxalate and dipropylene glycol methyl ester, or a combination of DBE, dimethyl oxalate, diethyl oxalate and dipropylene glycol methyl ether.

[0036] Preferably, the auxiliary agent includes a thickener, a thixotropic agent, a reinforcing agent, a dispersant, a leveling agent, a curing agent and a low-temperature active catalyst in a mass ratio of 1:(1-3):(1-3):(1-3):(1-3):(1-3):(1-3).

[0037] Preferably, the thickener comprises any one of ethyl cellulose, fumed silica, polyamide wax, polyvinyl alcohol or hydroxyethyl cellulose, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ethyl cellulose and fumed silica, a combination of polyamide wax and polyvinyl alcohol, a combination of polyamide wax, polyvinyl alcohol and hydroxyethyl cellulose, a combination of ethyl cellulose, fumed silica and polyamide wax, a combination of fumed silica, polyamide wax, polyvinyl alcohol and hydroxyethyl cellulose, or a combination of ethyl cellulose, fumed silica, polyamide wax, polyvinyl alcohol and hydroxyethyl cellulose.

[0038] Preferably, the thixotropic agent includes any one of BYK-410, BYK-420 or dibutyl phthalate, or a combination of at least two of them. Typical but non-limiting combinations include a combination of BYK-410 and BYK-420, a combination of BYK-420 and dibutyl phthalate, or a combination of BYK-410, BYK-420 and dibutyl phthalate.

[0039] Preferably, the reinforcing agent includes any one of latent isocyanate, tetraethyl titanate, methylimidazole, and benzyl glycidyl ether, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of latent isocyanate and tetraethyl titanate, a combination of methylimidazole and benzyl glycidyl ether, a combination of latent isocyanate, methylimidazole and benzyl glycidyl ether, or a combination of latent isocyanate, tetraethyl titanate, methylimidazole and benzyl glycidyl ether.

[0040] Preferably, the dispersant comprises any one of polyvinyl pyrrolidone, sodium dodecyl sulfate or Span 80, or a combination of at least two of them. Typical but non-limiting combinations include a combination of polyvinyl pyrrolidone and sodium dodecyl sulfate, a combination of sodium dodecyl sulfate and Span 80, a combination of polyvinyl pyrrolidone and Span 80, or a combination of polyvinyl pyrrolidone, sodium dodecyl sulfate and Span 80.

[0041] Preferably, the leveling agent includes any one of ethylene glycol butyl ether, silicone or acrylate or a combination of at least two thereof. Typical but non-limiting combinations include a combination of ethylene glycol butyl ether and silicone, a combination of silicone and acrylate, a combination of ethylene glycol butyl ether and acrylate, or a combination of ethylene glycol butyl ether, silicone and acrylate.

[0042] Preferably, the curing agent includes any one of EP-500, methyltetrahydrophthalic anhydride, dicyandiamide, 2-ethyl-4-methylimidazole, mercaptomercaptan, 2-phenylimidazole or acetylacetone transition metal complex or a combination of at least two thereof. Typical but non-limiting combinations include a combination of EP-500 and methyltetrahydrophthalic anhydride, a combination of dicyandiamide and 2-ethyl-4-methylimidazole, a combination of mercaptomercaptan and 2-phenylimidazole, a combination of dicyandiamide, 2-phenylimidazole and acetylacetone transition metal complex, a combination of EP-500, methyltetrahydrophthalic anhydride, dicyandiamide, 2-ethyl-4-methylimidazole and mercaptomercaptan, or a combination of EP-500, methyltetrahydrophthalic anhydride, dicyandiamide, 2-ethyl-4-methylimidazole, mercaptomercaptan, 2-phenylimidazole and acetylacetone transition metal complex.

[0043] Preferably, the low-temperature activated catalyst comprises any one of benzoic acid, n-decanoic acid, a fluorine-modified surfactant, a boron trifluoride complexing agent, dodecanoic acid, a silane coupling agent, p-phenylenediamine or stearic acid, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of benzoic acid and n-decanoic acid, a combination of n-decanoic acid and a fluorine-modified surfactant, a combination of a boron trifluoride complexing agent and dodecanoic acid, a combination of dodecanoic acid, a silane coupling agent, p-phenylenediamine and stearic acid, a combination of benzoic acid, n-decanoic acid, a fluorine-modified surfactant and a boron trifluoride complexing agent, a combination of boron trifluoride complexing agent, dodecanoic acid, a silane coupling agent, p-phenylenediamine and stearic acid, or a combination of benzoic acid, n-decanoic acid, a fluorine-modified surfactant, a boron trifluoride complexing agent, dodecanoic acid, a silane coupling agent, p-phenylenediamine and stearic acid.

[0044] In a second aspect, the present invention provides a method for preparing the conductive silver paste according to the first aspect, the preparation method comprising the following steps:

[0045] (1) mixing a resin and an organic solvent according to a formula amount to obtain a primary carrier;

[0046] (2) uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier;

[0047] (3) uniformly mixing the conductive silver and the secondary carrier obtained in step (2) according to the formula amount, grinding, and obtaining the conductive silver paste.

[0048] Preferably, the mixing temperature in step (1) is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] Preferably, the mixing time in step (1) is 4-8 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0050] Preferably, the mixing speed in step (1) is 800-1200 r / min, for example, it can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min or 1200 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0051] Preferably, the mixing temperature in step (2) is 18-25°C, for example, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the mixing speed in step (2) is 800-1200 r / min, for example, it can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min or 1200 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0053] Preferably, the mixing temperature in step (3) is 18-25°C, for example, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] Preferably, the mixing speed in step (3) is 800-1200 r / min, for example, it can be 800 r / min, 900 r / min, 1000 r / min, 1100 r / min or 1200 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0055] Preferably, the grinding in step (3) is performed by shear grinding using a three-roll grinder.

[0056] Preferably, the rotation speed of the shear grinding is 300-450r / min, for example, it can be 300r / min, 320r / min, 350r / min, 360r / min, 380r / min, 400r / min, 420r / min or 450r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the pressure between the rollers of the shear grinding is 18-48 MPa, for example, it can be 18 MPa, 20 MPa, 21 MPa, 24 MPa, 25 MPa, 27 MPa, 28 MPa, 30 MPa, 32 MPa, 35 MPa, 36 MPa, 40 MPa, 42 MPa, 45 MPa or 48 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] As a preferred technical solution of the preparation method according to the second aspect of the present invention, the preparation method comprises the following steps:

[0059] (1) Mixing the resin and the organic solvent according to the formula amount for 4-8 hours at 80-100° C. and a rotation speed of 800-1200 r / min to obtain a primary carrier;

[0060] (2) at 18-25° C. and a rotation speed of 800-1200 r / min, uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier;

[0061] (3) Under the conditions of 18-25° C. and a rotation speed of 800-1200 r / min, the conductive silver and the secondary carrier obtained in step (2) are uniformly mixed according to the formula amount, and shear grinding is performed using a three-roll grinder at a rotation speed of 300-450 r / min and an inter-roller pressure of 18-48 MPa to obtain the nanoimprint conductive paste.

[0062] In a third aspect, the present invention provides an application of the conductive silver paste as described in the first aspect, wherein the conductive silver paste is used for a metal grid flexible conductive film;

[0063] Preferably, the width of the wire grooves in the metal grid flexible conductive film is ≤2 μm, for example, 1 μm, 1.2 μm, 1.5 μm, 1.6 μm, 1.8 μm or 2 μm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0064] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] The present invention makes specific selection of resin types and specific setting of the ratio of resin to conductive silver, so that the final conductive silver paste has excellent conductivity, water boiling resistance and high weather resistance, and is suitable for conventional metal grid flexible conductive films with high requirements for light transmittance. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0068] Example 1

[0069] This embodiment provides a conductive silver paste, and the raw materials for preparing the conductive silver paste include:

[0070] Functional components 70 parts;

[0071] 4 parts of additives;

[0072] 26 parts of organic solvent;

[0073] The functional components include resin and conductive silver in a mass ratio of 1:9;

[0074] The resin is a saturated polyester resin (ES300) and an acrylic resin (BR-115) in a mass ratio of 5:1, the number average molecular weight of the saturated polyester resin is 40,000, and the number average molecular weight of the acrylic resin is 280,000;

[0075] The conductive silver is a mixture of micron silver flakes and nano silver powder in a mass ratio of 2:2; the thickness of the micron silver flakes is 1.5 μm, and the equivalent diameter is 3.5 μm; the particle size of the nano silver powder is in the range of 50-500 nm, and the median particle size D50 is 150 nm;

[0076] The organic solvent is dimethyl oxalate;

[0077] The auxiliary agents are a thickener, a thixotropic agent, a reinforcing agent, a dispersant, a leveling agent, a curing agent and a low-temperature active catalyst in a mass ratio of 1:1:1:1:1:1:1; the thickener is carboxymethyl cellulose; the thixotropic agent is BYK-410; the reinforcing agent is tetraethyl titanate; the dispersant is sodium dodecyl sulfonate; the leveling agent is ethylene glycol butyl ether; the curing agent is EP-500; and the low-temperature activated catalyst is benzoic acid;

[0078] The preparation method of the conductive silver paste described in this embodiment comprises the following steps:

[0079] (1) mixing the resin and the organic solvent according to the formula amount at 90° C. and a rotation speed of 1000 r / min for 6 hours to obtain a primary carrier;

[0080] (2) at 21° C. and a rotation speed of 1000 r / min, uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier;

[0081] (3) At 21° C. and a rotation speed of 1000 r / min, the conductive silver and the secondary carrier obtained in step (2) were uniformly mixed according to the formula amount, and shear grinding was performed using a three-roll grinder at a rotation speed of 360 r / min and a roller pressure of 30 MPa to obtain the nanoimprint conductive paste.

[0082] Example 2

[0083] This embodiment provides a conductive silver paste, and the raw materials for preparing the conductive silver paste include:

[0084] Functional components 66 parts;

[0085] 6 parts of additives;

[0086] 28 parts of organic solvent;

[0087] The functional components include resin and conductive silver in a mass ratio of 1:5;

[0088] The resin is a saturated polyester resin (ES300) and an acrylic resin (BR-115) in a mass ratio of 4:1, the number average molecular weight of the saturated polyester resin is 25000, and the number average molecular weight of the acrylic resin is 250000;

[0089] The conductive silver is a mixture of micron silver flakes and nano silver powder in a mass ratio of 2:1; the thickness of the micron silver flakes is 1 μm, and the equivalent diameter is 2 μm; the particle size of the nano silver powder is in the range of 50-500 nm, and the median particle size D50 is 100 nm;

[0090] The organic solvent is diethyl oxalate;

[0091] The auxiliary agent is a thickener, a thixotropic agent, a reinforcing agent, a dispersant, a leveling agent, a curing agent and a low-temperature active catalyst in a mass ratio of 1:1:1:1:1:1:1; the thickener is carboxymethyl cellulose; the thixotropic agent is BYK-420; the reinforcing agent is methylimidazole; the dispersant is Span 80; the leveling agent is acrylate; the curing agent is methyltetrahydropropionic anhydride; and the low-temperature activated catalyst is n-decanoic acid;

[0092] The preparation method of the conductive silver paste described in this embodiment comprises the following steps:

[0093] (1) mixing the resin and the organic solvent according to the formula amount for 4 hours at 80° C. and a rotation speed of 1200 r / min to obtain a primary carrier;

[0094] (2) at 18° C. and a rotation speed of 1200 r / min, uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier;

[0095] (3) At 18° C. and a rotation speed of 1200 r / min, the conductive silver and the secondary carrier obtained in step (2) are uniformly mixed according to the formula amount, and shear grinding is performed using a three-roll grinder at a rotation speed of 300 r / min and a roller pressure of 48 MPa to obtain the nanoimprint conductive paste.

[0096] Example 3

[0097] This embodiment provides a conductive silver paste, and the raw materials for preparing the conductive silver paste include:

[0098] Functional components 72 parts;

[0099] 3 parts of additives;

[0100] 25 parts of organic solvent;

[0101] The functional components include resin and conductive silver in a mass ratio of 1:12;

[0102] The resin is a saturated polyester resin (ES300) and an acrylic resin (BR-115) in a mass ratio of 6:1, the number average molecular weight of the saturated polyester resin is 50,000, and the number average molecular weight of the acrylic resin is 300,000;

[0103] The conductive silver is a mixture of micron silver flakes and nano silver powder in a mass ratio of 2:3; the thickness of the micron silver flakes is 3 μm, and the equivalent diameter is 5 μm; the particle size of the nano silver powder ranges from 50 to 500 nm, and the median particle size D50 is 200 nm;

[0104] The organic solvent is dipropylene glycol methyl ether;

[0105] The auxiliary agent is a thickener, a thixotropic agent, a reinforcing agent, a dispersant, a leveling agent, a curing agent and a low-temperature active catalyst in a mass ratio of 1:1:1:1:1:1:1; the thickener is carboxymethyl cellulose; the thixotropic agent is dibutyl phthalate; the reinforcing agent is benzyl glycidyl ether; the dispersant is sodium dodecyl sulfonate; the leveling agent is acrylate; the curing agent is 2-ethyl-4-methylimidazole; and the low-temperature activated catalyst is dodecanoic acid;

[0106] The preparation method of the conductive silver paste described in this embodiment comprises the following steps:

[0107] (1) Mixing the resin and the organic solvent according to the formula amount for 8 hours at 100° C. and a rotation speed of 800 r / min to obtain a primary carrier;

[0108] (2) at 25° C. and a rotation speed of 800 r / min, uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier;

[0109] (3) At 25° C. and a rotation speed of 800 r / min, the conductive silver and the secondary carrier obtained in step (2) are uniformly mixed according to the formula amount, and shear grinding is performed using a three-roll grinder at a rotation speed of 450 r / min and a roller pressure of 18 MPa to obtain the nanoimprint conductive paste.

[0110] Example 4

[0111] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the number average molecular weight of the saturated polyester resin is 22,000.

[0112] Example 5

[0113] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the number average molecular weight of the saturated polyester resin is 54,000.

[0114] Example 6

[0115] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the number average molecular weight of the acrylic resin is 220,000.

[0116] Example 7

[0117] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the number average molecular weight of the acrylic resin is 320,000.

[0118] Example 8

[0119] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the mass ratio of saturated polyester resin to acrylic resin is 3:1.

[0120] Example 9

[0121] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the mass ratio of saturated polyester resin to acrylic resin is 7:1.

[0122] Example 10

[0123] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the mass of micron silver flakes is replaced by the nano silver powder in Embodiment 1.

[0124] Embodiment 11

[0125] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the nano silver powder is replaced by the micron silver flakes in Embodiment 1.

[0126] Example 12

[0127] This embodiment provides a conductive silver paste, which is the same as that of Embodiment 1 except that the saturated polyester resin is replaced by ES100 with a data average molecular weight of 40,000.

[0128] Comparative Example 1

[0129] This comparative example provides a conductive silver paste, which is the same as Example 1 except that the saturated polyester resin is replaced by the acrylic resin in Example 1.

[0130] Comparative Example 2

[0131] This comparative example provides a conductive silver paste, which is the same as Example 1 except that the acrylic resin is replaced by the saturated polyester resin in Example 1.

[0132] Performance Testing

[0133] (1) At 25° C., the viscosity of the nanoimprint conductive pastes obtained in the above examples and comparative examples was tested using a digital viscometer VT-06. The results are shown in Table 1.

[0134] Table 1

[0135]

[0136]

[0137] (2) A substrate with a line groove width of 1.5 μm was provided, and the nanoimprint conductive pastes obtained in the above embodiment and comparative example were respectively filled in the line grooves, with a curing temperature of 150° C. and a curing time of 40 min to obtain a metal grid flexible conductive film.

[0138] The adhesion between the cured nanoimprint conductive paste and the substrate was tested using the Baige method;

[0139] The square resistance, water boiling resistance, high temperature and high humidity resistance, thermal shock resistance, salt spray resistance and bending resistance of the obtained metal grid flexible conductive film were tested;

[0140] Use a multimeter to test the square resistance;

[0141] The test method for water boiling resistance is: use a water bath to boil at 100℃ for 30 minutes, and then use the hundred-grid method to test the adhesion;

[0142] The test method for high temperature and high humidity resistance is to place the obtained metal grid flexible conductive film in an environment with a temperature of 85° C. and a relative humidity of 85% for 1200 hours, and then test the adhesion according to the hundred-grid method.

[0143] The test method for the resistance to cold and hot shock performance is to place the obtained metal grid flexible conductive film in a cold and hot shock box for 1200 hours. The temperature in the cold and hot shock box is cycled in the range of -48°C to 80°C with a cycle of 4 hours, and then the adhesion is tested according to the 100-grid method.

[0144] The test method for salt spray resistance is to place the obtained metal grid flexible conductive film in a hot and cold shock box, perform a 5% NaCl salt spray test at 35°C for 42 hours, and then test the adhesion according to the hundred-grid method.

[0145] The testing method for the bending resistance is to fold the obtained metal grid flexible conductive film in half for 1 minute, and then test the adhesion according to the hundred-grid method.

[0146] The results are shown in Table 2 and Table 3.

[0147] Table 2

[0148]

[0149]

[0150] Table 3

[0151]

[0152]

[0153] It can be seen from Table 2 and Table 3 that the conductive silver paste provided in the present application has excellent conductivity, and excellent water boiling resistance and weather resistance.

[0154] From the comparison between Examples 4-5 and Example 1, it can be seen that when the number average molecular weight of the saturated polyester is not in the range of 25000-50000, when the obtained conductive silver paste is used for the metal grid flexible conductive film, its conductive performance, boiling resistance and weather resistance are significantly reduced.

[0155] From the comparison between Examples 6-7 and Example 1, it can be seen that when the number average molecular weight of acrylic acid is not in the range of 250,000-300,000, when the obtained conductive silver paste is used for the metal grid flexible conductive film, its conductive performance, water boiling resistance and weather resistance are significantly reduced.

[0156] From the comparison between Examples 8-9 and Example 1, it can be seen that when the mass ratio of saturated polyester resin to acrylic acid is not within the range of (4-6):1, when the obtained conductive silver paste is used for the metal grid flexible conductive film, its conductive performance, water boiling resistance and weather resistance are significantly reduced.

[0157] Comparison between Examples 10 and 11 and Example 1 shows that when the conductive silver is only nano silver powder or micron silver flakes, the conductive performance, boiling resistance and weather resistance of the obtained conductive silver paste when used for the metal grid flexible conductive film are significantly reduced.

[0158] From the comparison between Comparative Examples 1 and 2 and Example 1, it can be seen that the resin in the conductive silver paste needs to be a combination of saturated polyester resin and acrylic resin, and neither of them can be missing.

[0159] In summary, the present invention, through the specific selection of resin types and the specific setting of the ratio of resin to conductive silver, makes the final conductive silver paste have excellent conductivity, water boiling resistance and high weather resistance, and is suitable for conventional metal grid flexible conductive films with high requirements for light transmittance.

[0160] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of conductive silver paste in a metal grid flexible conductive film with a line slot width of ≤2μm, characterized in that: In parts by weight, the raw materials for preparing the conductive silver paste are: 66-72 parts of functional components; 3-6 parts of additives; 25-28 parts of organic solvent; The functional component is a resin and conductive silver in a mass ratio of 1:(5-12); The resins are saturated polyester resin and acrylic resin; the mass ratio of the saturated polyester resin to the acrylic resin is (4-6):1; the number average molecular weight of the saturated polyester resin is 25000-50000; the number average molecular weight of the acrylic resin is 250000-300000; The conductive silver is a micron silver flake and a nano silver powder in a mass ratio of 2:(1-3); the thickness of the micron silver flake is 1-3 μm, and the equivalent diameter is 2-5 μm; the particle size range of the nano silver powder is 50-500 nm, and the median particle size D50 is 100-200 nm; The auxiliary agent is a thickener, a thixotropic agent, a reinforcing agent, a dispersant, a leveling agent, a curing agent and a low-temperature active catalyst in a mass ratio of 1:(1-3):(1-3):(1-3):(1-3):(1-3); the thickener is any one of ethyl cellulose, fumed silica, polyamide wax, polyvinyl alcohol or hydroxyethyl cellulose or a combination of at least two of them; the thixotropic agent is any one of BYK-410, BYK-420 or dibutyl phthalate or a combination of at least two of them; the reinforcing agent is any one of latent isocyanate, tetraethyl titanate, methylimidazole, benzyl glycidyl ether or a combination of at least two of them The dispersant is any one of polyvinyl pyrrolidone, sodium dodecyl sulfate or Span 80 or a combination of at least two thereof; the leveling agent is any one of ethylene glycol butyl ether, silicone or acrylate or a combination of at least two thereof; the curing agent is any one of EP-500, methyltetrahydrophthalic anhydride, dicyandiamide, 2-ethyl-4-methylimidazole, mercaptothiol, 2-phenylimidazole or acetylacetone transition metal complex or a combination of at least two thereof; the low-temperature activated catalyst is any one of benzoic acid, n-decanoic acid, fluorine-modified surfactant, boron trifluoride complexing agent, dodecanoic acid, silane coupling agent, p-phenylenediamine or stearic acid or a combination of at least two thereof.

2. The use of the conductive silver paste according to claim 1 in a metal grid flexible conductive film with a line groove width of ≤2 μm, characterized in that: The organic solvent includes any one of DBE, dimethyl oxalate, diethyl oxalate or dipropylene glycol methyl ether, or a combination of at least two thereof.

3. The use of the conductive silver paste according to claim 1 or 2 in a metal grid flexible conductive film with a line slot width of ≤2 μm, characterized in that: The preparation method of the conductive silver paste comprises the following steps: (1) mixing a resin and an organic solvent according to a formula amount to obtain a primary carrier; (2) uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier; (3) uniformly mixing the conductive silver and the secondary carrier obtained in step (2) according to the formula amount, grinding, and obtaining the conductive silver paste.

4. The use of the conductive silver paste according to claim 3 in a metal grid flexible conductive film with a line groove width of ≤2 μm, characterized in that: The mixing temperature in step (1) is 80-100° C. The mixing time in step (1) is 4-8 hours; The mixing speed in step (1) is 800-1200 r / min; The mixing temperature in step (2) is 18-25° C. The mixing speed in step (2) is 800-1200 r / min; The mixing temperature in step (3) is 18-25°C; The mixing speed in step (3) is 800-1200 r / min.

5. The use of the conductive silver paste according to claim 3 in a metal grid flexible conductive film with a line groove width of ≤2 μm, characterized in that: The grinding in step (3) is performed by shear grinding using a three-roll grinder; The rotation speed of the shear grinding is 300-450r / min; The pressure between the rollers of the shear grinding is 18-48 MPa.

6. Application of the conductive silver paste according to claim 4 or 5 in a metal grid flexible conductive film with a line slot width of ≤2 μm, characterized in that: The preparation method comprises the following steps: (1) Mixing the resin and the organic solvent according to the formula amount for 4-8 hours at 80-100° C. and a rotation speed of 800-1200 r / min to obtain a primary carrier; (2) at 18-25° C. and a rotation speed of 800-1200 r / min, uniformly mixing the auxiliary agent and the primary carrier obtained in step (1) according to the formula amount to obtain a secondary carrier; (3) Under the conditions of 18-25° C. and a rotation speed of 800-1200 r / min, the conductive silver and the secondary carrier obtained in step (2) are uniformly mixed according to the formula amount, and shear grinding is performed using a three-roll mill at a rotation speed of 300-450 r / min and a roller pressure of 18-48 MPa to obtain the conductive silver paste.

Citation Information

Patent Citations

  • Flexible conductive silver paste and manufacturing method

    CN105702323A

  • Conductive silver paste for flexible circuit and preparation method of conductive silver paste

    CN112908513A

  • Wear-resistant conductive paste and preparation method thereof

    CN113436781A